PERAN ZAKAT SEBAGAI PENDORONG MULTIPLIER EKONOMI - Ali Hardana (Institut Agama Islam Negeri Metro, 2023)
The number of poor Muslim people always increases. Education and income gaps are regarded as the cause of the poor getting poorer and the rich get richer. It is the responsibility of Muslims to help each other to alleviate poverty through performing and empowering the zakat. Zakat plays an essential role in the economy, especially in reducing poverty. The existence of zakat will increase aggregate demands from mustahiq raise; then it will increase aggregate supply and employment. This is known as an economic multiplier. The well-managed zakat will bring about the great benefit of zakat in the economy, especially in overcoming the poor.